PERTIMBANGAN HAKIM ATAS TINDAK PIDANA PENCURIAN DENGAN MODUS CARDING BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Ida R Hasan (Jurnal Ilmiah Advokasi, 2022)
The development of a human financial life evolves following the times that are influenced by cyber space where everything is easy and instant, one of which is the use of debit/credit cards where this card offers convenience in carrying out various transactions without having to use cash and is very efficient to handle. anywhere even in large numbers. The development of the need for payment instruments using debit/credit cards has become a prima donna in the community. However, the presence of the debit/credit card does not mean that it does not present problems, behind it all there is a gap for someone to commit a crime. Therefore, this crime mode using a debit/credit card or carding can be done through various computer programs to steal, forge or obtain a debit/credit card, how to create fake debit/credit card numbers, how to duplicate a debit/credit card legal, and how to use a fake debit/credit card. The crime of carding has grown rapidly in Indonesia, meanwhile the Indonesian legal system has gaps and weaknesses in the monitoring and regulation system and law enforcement in this crime.Keywords: Cyber Crime, Crime of Theft, Carding